Penerapan Metode Weighted Product Dalam Sistem Pendukung Keputusan Pemberian Reward PT. Mitra - Audina, Mia Divia; Pratama, Dicky (Universitas Multi Data Palembang, 2025)
PT. Mitra Anugerah Perkasa is a company operating as a distributor of subsidized and non-subsidized fertilizers in South Sumatra. Apart providing basic salaries to employees, PT. Mitra Anugerah Perkasa provides rewards of salary increases and bonuses for employee. Rewards are given by assessing employee performance through monthly assessments and then giving rewards once a year. The assessment process that has been carried out is not effective because many aspects have to be calculated manually, which takes a lot of time and allows errors. The aim of developing this system is to build a decision support system (DSS) using the Weighted Product (WP), with the aim of simplifying the assessment process. This application was created based on a website using the Laravel framework with a Rational Unified Process (RUP) system. The results obtained show that system can increase efficiency of performance assessment, provide measurable transparent weights, and meet stated research objectives.